The Effectiveness of Using FOTOKIT as a Teaching Aid for Front Office Subject in Community College - Anak Kok Roseline; Quah Wei Boon (Universitas Muhammadiyah Sidoarjo, 2019)
This paper aims to investigate the effectiveness of using FOTOKIT as a teaching aid for front office subject in community college. Specifically, this study has three objectives, namely: (i) To identify students' perceptions of using FOTOKIT as a teaching aid for Front Office subject in community college; (ii) To determine the relationship between the effectiveness of using FOTOKIT and products assessment; (iii) To determine the differences in the effectiveness of using FOTOKIT as a teaching aid for front office subject in community college based on gender. A total of 54 respondents, the Sungai Petani Community College students were selected to answer the questions in the questionnaires distributed by the researchers. This data has been analyzed using Statistical Package for Social Science (SPSS) Version 21.0. The results showed that the level of perception of students on the use of FOTOKIT as a teaching aid for Front Office subject in community college was at high level (M = 4.72, SP = .31). T-test found that there was no significant difference between gender and the effectiveness of FOTOKIT as a teaching aid for Front Office subject in community college, p> .05. The Pearson Correlation Test found that there was a strong (positive) relationship between the effectiveness of using FOTOKIT with the product assessment (r = .700, p <.01). In conclusion, the innovation of FOTOKIT still can be improved in order to enhance students learning performance in Front Office subject.